Validation of a new experimental model of extrusive luxation on maxillary molars of rats: a histological study - Costa, Luciana Artioli [UNESP]; Cantanhede, Luana Martins; Pereira, Erika Martins; Crivelini, Marcelo Macedo [UNESP]; Cuoghi, Osmar Aparecido [UNESP]; Pereira, Alex Luiz Pozzobon; de Mendonça, Marcos Rogério [UNESP] (My University, 2018)
Background/aim: The aim of this study was to test and validate a new model of extrusive luxation trauma on maxillary first molars of rats. Material and methods: Forty adult male rats (Rattus norvegicus albinus, Wistar; weight = 230–250 g), 45 days old, were divided into eight groups (n = 5): control groups, in which animals were not subjected to any procedure and waited 1 day (GC1D) or 3 days (GC3D) for euthanasia, and experimental groups, in which animals were subjected to forces of 1100cN, 1300cN, or 1500cN and waited 1 or 3 days for euthanasia (GT1100/1D, GT1100/3D, GT1300/1D, GT1300/3D, GT1500/1D, GT1500/3D). In animals of the experimental groups, trauma was produced by an extrusive force in maxillary first right molars. Four-micrometer serial cuts stained with hematoxylin and eosin (HE) were made. Descriptive microscopic analysis of first upper right molar and semi-quantitative analysis (scores 1 to 4) of intensity of acute and chronic inflammation and vascular changes in the periodontal ligament and active and inactive external root resorption were conducted. The distribution of scores in the groups was compared using the Freeman-Halton extension of Fisher’s exact test. The significance level was 5%. Results: It was observed that vascular disorders (bleeding) on the periodontal ligament became more evident with increasing extrusive force. Conclusions: This new method was capable of generating histological changes, proving its secure application in this research area. The 1500cN force produced more damage on the periodontal ligament. Clinical relevance: The validation of a new experimental method can produce more reliable evidence in further research.
Keywords: Animal; Dental trauma; Models; Tooth injuries; Validation studies